Anion‐Induced Catalytic Reaction in a Solution‐Processed Molybdenum Oxide for Efficient Inverted Ternary Organic Photovoltaics. (25th June 2022) - Ki, Taeyoon; Lee, Changhoon; Kim, Jehan; Hwang, In‐Wook; Oh, Chang‐Mok; Park, Kiyoung; Lee, Sanseong; Kim, Ju‐Hyeon; Balamurugan, Chandran; Kong, Jaemin; Jeong, Hyeon‐Seok; Kwon, Sooncheol; et al.
Abstract: Solution‐processed transition metal oxides (TMOs) prepared from complex ion precursors are developed as promising scalable interfacial layers for non‐fullerene organic photovoltaics (OPVs); however, challenges remain in achieving defect‐free and highly oriented metal‐oxygen networks without post‐deposition treatments due to the presence of residual organic metal‐binding ligands in films. Herein, the novel strategy that the problematic organic metal‐binding ligands in TMO precursors can be successfully eliminated by an anion‐induced catalytic reaction (ACR) at room temperature is demonstrated, in which the low‐level anions induce electron redistribution and instability of TMO precursors, expediting binding ligand removal during the hydrolysis reaction. The subsequent condensation process facilitates a dimensionally confined and continuous metal‐oxygen network with a 20‐fold increase in electrical conductivity (from 8.4 × 10 −4 to 1.8 × 10 −2  S m −1 ) and superior work function tunability (from 5.1 to 5.3 eV) compared to the pristine film. The ACR‐derived TMO thin film on top of a ternary PBDB‐TF:Y6:PC71 BM photoactive layer enables an inverted device configuration with improved efficiency of 17.6%, as well as enhanced stability over 70% of the initial efficiency for up to 100 h AM 1.5G illumination. Abstract : A room temperature sol‐gel processed MoO x is developed for highly efficient and stable inverted organic photovoltaics via an anion‐induced catalytic reaction (ACR). The ACR‐derived MoO x thin film exhibits a defect‐free and highly oriented metal‐oxygen network without post‐treatment, enabling outstanding physical and electrical properties on top of the organic photoactive layer.